Strengthening Elementary School Students’ Mental Health Through Wise and Safe Digital Literacy - Jati, Sutopo Patria; Budiyanti, Rani Tiyas; Nandini, Nurhasmadiar; Kusumastuti, Wulan; Arso, Septo Pawelas (Jurnal Pengabdian West Science, 2025)
The development of digital technology can provide benefits for its users; however, if not used wisely, it can have negative impacts, such as mental health issues. Several problems can arise, such as anxiety disorders, depression, sleep disorders, and low self-esteem, which can be related to the use of digital technology such as social media. Wise and safe use of social media, good digital literacy, and the role of parents and teachers are needed to support the use of this digital media so that it can have a positive impact. The implementation of education related to wise and safe digital literacy was carried out at the Bina Insani Integrated Islamic Elementary School in Semarang City, and received quite positive feedback and quite high enthusiasm. This community service is expected to improve education related to digital literacy for elementary school-aged children.